The relationship between training and organizational commitment among academicians in Malaysia - Bashir, Nouruddeen (Emerald Group Publishing Ltd., 2015)
Purpose – The purpose of this paper is to address the question “what is the relationship between employees’ perception on training and employees’ organisational commitment?” using the widely accepted theories of three-component model of organisational commitment and training-related variables. Design/methodology/approach – This study utilises the survey methodology approach. The study design is an associational descriptive research designed to identify the relationship between employees’ training measured by five training variables (perceived availability of training, motivation to learn in training, perceived co-worker support for training, perceived supervisor support for training and perceived benefits of training) and employees’ organisational commitment measured by three organisational commitment components (affective commitment, continuance commitment and normative commitment). The target population of this study consisted of academic staffs of one of the faculty in a public university in Malaysia. The name of the University is not disclosed due to the request from the management of the University. Comprehensive sampling approach was used in this survey, whereby the survey was distributed to all the target population. This approach was chosen to ensure higher response rate from the respondents. The target population is academic staff and 60 responses were analysed. Findings – Findings from the study revealed a significant and positive relationship between the training-related variables (availability of training, motivation to learn, co-worker support for training, supervisor support for training and benefits of training) the affective and normative commitment components of the organisational commitment; while a non-significant relationship with continuance commitment. Additionally, the results of the study revealed that the best predictor of affective commitment is co-worker support for training followed by availability of training. For normative commitment, the best predictor was availability of training. Research limitations/implications – Although this study was conducted in the education industry, the results of this study were consistent with previous studies conducted in western countries and the few studies conducted in some Asian countries such as Qatar, China, Australia and Malaysia that are non-education industries. However, the study was conducted in a single university in Malaysia and therefore results of the study may not be generalisable to all higher institutions nor the universities excluded in the sample. The study was limited to academic staffs, and does not involve other employees such as non-academic staff. Therefore the result may not be generalisable to those excluded staff as training policies, skills and knowledge requirement among various staff categories differ. Practical implications – This study has indicated that co-worker support for training and supervisor support of training enhance emotional attachment/sense of belonging (i.e. affective commitment) and loyalty (i.e. normative commitments) among academic staff. Thus in this view the university authority could create an environment where there is a strong encouragement by colleagues and supervisors towards participating in training activities. Supervisors in the context of this study refer to HoDs, Deans, head of research groups, etc. This research has also revealed that availability (or access) to training has a strong relationship with both affective and normative commitments; with availability of training a strong predictor of the former type of commitment. Therefore the university through supervisors can play a role in publicising the availability of training to the academic staff. The university can also design more in-house training and development programmes/activities as well as encourage and financially support external training programmes that will enhance the academic staff teaching and research skills. Such move by the university could be perceived by the academic staff as support and care which ultimately leads to better organisational performance. Originality/value – This is a pioneering study on perception on training towards organisational commitment among academic staff in a public university in Malaysia. The result of this study will spur public universities in Malaysia to find ways to improve their training plan and design to achieve maximum satisfaction among the academician.